Ergonomic risk analysis between servants during the execution of foundations - Souza Oliveira, Flávia (2018)
This research has the objective of evaluating the ergonomic risks to which the servants are exposed during the execution of foundations, in a construction site. It is characterized as an exploratory-descriptive and quantitative study. The results allowed verifying the precariousness of technologies directed to the work activities performed by the servants. It is suggested, therefore, that construction companies adopt economically viable measures to minimize the ergonomic risks to which these professionals are exposed, contributing to the improvement of the quality of life at work as well as the increase of organizational productivity.